Pengembangan Media Pembelajaran Smart Board dengan Pendekatan PMRI pada Materi Bilangan Bulat - Mardhiyah, Elok Izzatul; Qohar, Abd; Anwar, Lathiful (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2023)
Learning can run well if the components contained in it work together and support each other to achieve learning goals. This study aims to develop Smart board learning media with the Indonesian Realistic Mathematics Education (PMRI) approach on integer material that is valid and practical. This study uses the Research and Development (R&D) method. The subjects of this study were students of class VI MI in Malang City. This type of research is development research, where the instruments used include interview sheets, material expert validator questionnaires, media experts and student response questionnaires. Through these instruments, data is obtained that will be analyzed to find out whether the learning media that have been made are suitable for use in the learning process. The development model used is the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The results of the validation of material experts and media experts show that the media meets valid criteria with an average score of 3.71. The results of the student questionnaire show that the media is stated to be practical with the criteria for an average score of the student questionnaire results of 3.68. Based on the results of this analysis, Smart board learning media on integer material can be declared valid and practical. During the learning process, students can more easily understand the material presented because it uses interesting and not boring media. So that the learning media that are made are suitable for use in the learning process, especially on integer material.